A nationwide survey of clinical characteristics, management, and outcomes of acute kidney injury (AKI) – patients with and without preexisting chronic kidney disease have different prognoses. Issue 39 (September 2016) - Pan, Heng-Chih; Wu, Pei-Chen; Wu, Vin-Cent; Yang, Ya-Fei; Huang, Tao-Min; Shiao, Chih-Chung; Chen, Te-Chuan; Tarng, Der-Cherng; Lin, Jui-Hsiang; Yang, Wei-Shun; Sun, Chiao-Yin; Lin, Chan-Yu; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Acute kidney injury (AKI) is a common complication in hospitalized patients. The International Society of Nephrology implemented the "0 by 25" initiative aimed at preventing deaths from treatable AKI worldwide by 2025 and conducted a global snapshot survey in 2014. We joined in the project and conducted this study to compare the epidemiology, risk factors, and prognosis between patients with pure AKI and those with acute-on-chronic kidney disease (ACKD). In this study, we prospectively collected demographic parameters and data on clinical characteristics, baseline comorbidities, management, and outcomes of 201 AKI patients in 18 hospitals in Taiwan from September 2014 to November 2014. The in-hospital mortality rate was 16%. AKI was mostly attributed to sepsis (52%). Multivariate logistic regression indicated that oliguria was a positive independent predictor of in-hospital mortality, whereas preexisting CKD and exposure to nephrotoxic agents were negative independent predictors. The prevalence of vasopressor use, intensive care unit care, and mortality were significantly higher in pure AKI patients than in ACKD patients. Moreover, serum creatinine (SCr) levels significantly increased within 7 days after AKI diagnosis in nonsurvivors but not in survivors in the pure AKI group. By contrast, SCr levels were persistently lower in nonsurvivors than in survivors in the ACKD group during the same period. We thus determined that the prognosis of ACKD patients differed from that of pure AKI patients. Considering the CKD history in the future AKI staging system may improve prognosis prediction.